Analysis of The Meanings of The Khafd Letter "Lam" in The Holy Qur’an - Wahyuni, Septi (Al-Muyassar: Journal of Arabic Education, 2024)
This writing examines the types of meanings of the letter “Lam” in verses of the Qur’an. The interest of knowledge in terms of increasing the meaning of the letter Khafs is specific to the letter “Lam”, including: to know the meanings of the word in the Qur’an as a rule that fits the sentences, to know the meanings of the verses of the Qur’an in general, and to know one of the wonders of the Qur’an with its highest and most beautiful composition. Jamal al-Din bin Hisham says in Mughni al-Labib that the basic meanings of the letter al-khafs “lam” are all 21, including: entitlement, approval, ownership, possession, quasi-ownership, affirmation of negation, the meaning of to, the meaning of Ali (true superiority), the meaning of in, the meaning of at, reasoning, the meaning of after, the meaning of with, the meaning of who, and attainment. The meaning of 'an, the procession, exclamation with an oath, exclamation without an oath, transitivity, and emphasis (the extra letter). Accordingly, every word beginning with the letter “Lam” has additional meanings, is emphasized with various meanings, and clarifies the basic meanings of the basic sentence clause by adding the letter “Lam” until the letter “Lam” is the first word in the appropriate sentence option.Keywords: The Qur’an, basic meanings of the letter “Lam